Lineage-specific variations in the trigger loop modulate RNA proofreading by bacterial RNA polymerases - Esyunina D; Turtola M; Pupov D; Bass I; Klimašauskas S; Belogurov G; Kulbachinskiy A (Oxford Univ Press, 2022)
RNA cleavage by bacterial RNA polymerase (RNAP) has been implicated in transcriptional proofreading and reactivation of arrested transcription elongation complexes but its molecular mechanism is less understood than the mechanism of nucleotide addition, despite both reactions taking place in the same active site. RNAP from the radioresistant bacterium Deinococcus radiodurans is characterized by highly efficient intrinsic RNA cleavage in comparison with Escherichia coli RNAP. We find that the enhanced RNA cleavage activity largely derives from amino acid substitutions in the trigger loop (TL), a mobile element of the active site involved in various RNAP activities. The differences in RNA cleavage between these RNAPs disappear when the TL is deleted, or in the presence of GreA cleavage factors, which replace the TL in the active site. We propose that the TL substitutions modulate the RNA cleavage activity by altering the TL folding and its contacts with substrate RNA and that the resulting differences in transcriptional proofreading may play a role in bacterial stress adaptation.